Meta-Analysis: Validity and Practicality of Student Worksheet Development (LKPD) Oriented Project Based Learning (PjBL - Lufri; Radhifah (INSTITUT AGAMA ISLAM NEGERI AMBON, 2024)
The learning process is gradual, starting from simple to complex, with an emphasis on the use of learning media such as LKPD. One learning model that can be used to vary the LKPD is the Project Based Learning (PjBL) model. This model can increase student engagement and interaction while increasing their drive to learn biology concepts. The aim of this research is to evaluate the validity and practicality of PjBL-based LKPD. The research method is meta-analysis, which is a technique that involves the collection of related articles from relevant sources, namely Google Scholar. Fifteen artivles related to the development of PjBL-based LKPD. Based on the results of the analysis, the development of PjBL-based LKPD meets the criteria of being very valid and very practical so it is suitable for use in learning. The research findings produced an average practicality score of 89.71% in the very practical category and an average validity score of 89.58% in the very valid category. Keywords: Student Worksheet, Meta-Analysis, Project Based Learning